Accessory breast - an anomaly to live with: A case report and literature review - Golubović Jelena; Nikčević Suzana; Jeličić Sandra; Supić Svetlana; Pantić Milica; Đorđević Marjana; Kostić Andrija (Vojnosanitetski Pregled)
Introduction. During normal fetal development, between the second and third months of gestation, the thoracic ridge forms from the milk line on the front part of the chest at the level of the fourth intercostal space, while the remaining parts involute. If this tissue fails to involute, ectopic breast tissue develops, with or without the nipple-areola complex. Case report. We present a 50-year-old female patient who was examined for pain in the right breast region one month after a traffic accident. The performed clinical examination, ultrasound, and mammography confirmed the presence of an accessory breast along the left inframammary milk line without any pathological changes. Throughout her life, the patient has experienced no issues with her breasts or other organ systems, except for cholecystitis, for which she underwent gallbladder surgery several years ago. Given that the patient has had no problems so far, she was advised to have a breast ultrasound in one year and a mammogram in two years. Conclusion. An accessory breast is a congenital anomaly of breast tissue that clinicians should consider in patients presenting with marked subcutaneous tissue tumefaction in the mammary line region, along with an appropriate clinical picture. Since all diseases affecting normal breast tissue can also affect accessory breasts, their timely clinical recognition and treatment are necessary.